Albiglutide Does Not Prolong QTc Interval in Healthy Subjects: A Thorough ECG Study - Darpo, Borje (Springer Healthcare, 2014)
INTRODUCTION: Albiglutide, a selective once-weekly glucagon-like peptide-1 receptor agonist, is being developed for the treatment of type 2 diabetes mellitus. Albiglutide’s effect on cardiac repolarization (QTc interval) was assessed in a randomized, double-blind, placebo-controlled, parallel-group study in healthy subjects with a nested crossover comparison for moxifloxacin. METHODS: Subjects were randomized to albiglutide (n = 85) or placebo (n = 89) and received injections of 30 mg albiglutide or placebo on Days 1 and 8 and 50 mg albiglutide or placebo on Days 15, 22, 29, and 36. In the placebo group, moxifloxacin was administered on Day −1 in half the subjects and on Day 40 in the other half. Blood samples for albiglutide plasma concentration were drawn on Days 4 and 39 and serial ECGs were extracted from continuous recordings on Days −2 (baseline), −1, 4, 39, and 40. RESULTS: Demographics were generally similar between albiglutide and placebo subjects: mean age was 29 years and BMI 25 kg/m(2). Mean change-from-baseline QTcI (∆QTcI, which was corrected for individual heart rate) on Day 4 after a single dose of albiglutide 30 mg and on Day 39 after repeat dosing with albiglutide 50 mg once weekly was similar to the placebo response. The placebo-corrected ΔQTcI (ΔΔQTcI) on both albiglutide doses was small with the largest ΔΔQTcI of 1.1 ms (upper bound of 90% CI 3.8 ms) on Day 4 and −0.6 ms (upper bound of CI 1.8 ms) on Day 39. Moxifloxacin caused the largest mean effect on ΔΔQTcI of 10.9 ms and the lower bound of the CI was above 5 ms at all preselected timepoints, thereby demonstrating assay sensitivity. Albiglutide was well tolerated and there were no clinically relevant differences in safety data between albiglutide and placebo. CONCLUSION: Albiglutide at doses up to 50 mg in healthy subjects did not prolong the QTc interval. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s13300-014-0055-1) contains supplementary material, which is available to authorized users.